Draft Annual Plan 1987-88 Seventh Five Year Plan 1985-90 Union Territory of Pondicherry - Planning Commission (Planning Commission, 1987)
The Scheme has been taken up in this Union Territory so as to protect the cattle population against Rinderpest Diseases. As this territory has got innumerable point of entry of cattle, the cattle movement has to be screened by doing vaccination as far as possible. For this purpose, a check post was started functioning since 1981 at Pondicherry- Villupuram road; which is the main point of entry of cattle. It is contemplated that one similar check post at Pondicherry- Cuddalore road during the Seventh Five Year Plan.
Government of Pondicherry, Planning and Research Department